Culture of brand origin (COBO): the impacts of language and linguistics on purchase intention of a brand - Amran Harun; Nabsiah Abdul Wahid; Osman Mohamad; Jaratin Lily; Charlie Albert Lasuin (MCSER-Mediterranean Center of Social and Educational Research, 2016)
This paper provides new insights into origin effect by focusing on new significant parameters pertaining to culture namely language and linguistics factors. It is postulated that the identification of culture of brand origin (COBO) on the basis of its language, and evaluation on linguistics components in a brand name can influence consumers to purchase a brand. The study is quantitative in nature using a survey method on consumer samples on which they were asked to evaluate food products sold under four different Malaysian brand names whereby each brand name is representing four different languages (i.e., Bahasa Malaysia, Mandarin, Tamil and English) that are used for communication within the major ethnic groups in the country. Results from a survey of 504 working adults comprised of Malay, Chinese and Indian respondents indicated that the elements in COBO have an influence on consumers’ purchase intention. The study findings imply the importance of COBO as a tool to predict consumer’s intention to purchase by using linguistic components found in product’s brand name. Managers can appreciate the usefulness of language as a strategy in brand positioning and determining the most effective linguistic pattern to be applied in a brand name. Usefulness of language as a strategy in brand positioning and determining the most effective linguistic pattern to be applied in a brand name.